Continuous Microfiber Wire Mandrel‐Less Biofabrication for Soft Tissue Engineering Applications (Adv. Healthcare Mater. 13/2022). Issue 13 (6th July 2022) - Adamo, Arianna; Bartolacci, Joseph G.; Pedersen, Drake D.; Traina, Marco G.; Kim, Seungil; Pantano, Antonio; Ghersi, Giulio; Watkins, Simon C.; Wagner, William R.; Badylak, Stephen F.; D'Amore, Antonio
Abstract : Medical Textiles In article number 2102613, Antonio D'Amore and co‐workers introduce a novel mandrel‐less fabrication methodology for polymeric wires, with a circular cross‐section, unlimited length, and controllable microarchitecture. The use of this fabrication apparatus allows for the production of microfiber bundles with tunable ultrastructure and mechanical properties that can be used as suture materials and as tissue surrogates for tendon and ligament repair.